‘Who Gives You the Power to Get Wealth’: Economics and the Hebrew Bible in the Past Decade - Noya, Ludwig Beethoven J. (Currents in biblical research, 2024)
This article presents an overview of scholarship related to the economy in Hebrew Bible studies, focusing particularly on scholarship published in the past decade (2013–2023). For the scholarship before this past decade, please see Nam’s excellent survey on the topic in Portrayals of Economic Exchange in the Book of Kings (2012: 17–70) and in ‘Economics and the Bible’ (2013). The article has three sections. The first explores recent discussions on various models proposed to understand the economic situation of the world behind the Hebrew Bible. The second outlines recent discussions on the components of production; namely, land access, labor relations, and the role of debt in connecting the two. The third and final section surveys scholarship on two interrelated elements responsible for the flow of resources: temple and royal administration.